Vascularized Ribs in the Treatment of Posterior Instrumentation Infection after Thoracic Vertebrectomy. Case Report - Cavadas, Pedro C.; Baklinska, Magdalena; Téllez, Daniela (Indian Journal of Plastic Surgery, 2022)
Isolated vertebral mestastases can be successfully treated by surgical removal of the affected vertebral body and stabilization with alloplastic material. The bone union between the upper and lower vertebra is expected, yet a relatively high rate of a non-union has been reported. In case of infection, bone consolidation is altered, and removal of alloplastic material is recommended, which decreases spinal stability and is a devastating complication.This case report of delayed infection and exposure of posterior hardware after thoracic vertebrectomy without an interbody osseous union, authors present a successful treatment with vascularized rib flaps through an anterior approach followed by hardware removal.
Keywords: Vertebrectomy For Bone Metastasis; breast cancer; septic vertebral non-union; vascularized ribs; posterior instrumentation